Ethanol-Induced Alterations in Placental and Fetal Cerebrocortical Annexin-A4 and Cerebral Cavernous Malformation Protein 3 Are Associated With Reductions in Fetal Cortical VEGF Receptor Binding and Microvascular Density - Savage, Daniel D.; Rosenberg, Martina J.; Coquet, Laurent; Porch, Morgan W.; Allen, Nyika A.; Roux, Christian; Aligny, Caroline; Jouenne, Thierry; Gonzalez, Bruno J. (Frontiers in Neuroscience, 2020)
Gonzalez and colleagues have reported prenatal alcohol exposure (PAE)-induced reductions of angiogenesis-related proteins in mouse placenta. These effects were associated with striking alterations in microvascular development in neonatal cerebral cortex. Here, we employed a rat model of moderate PAE to search for additional proteins whose placental and fetal cortical expression is altered by PAE, along with a subsequent examination of fetal cerebral cortical alterations associated with altered protein expression. Long-Evans rat dams voluntarily consumed either a 0% or 5% ethanol solution four hours each day throughout gestation. Daily ethanol consumption, which resulted in a mean peak maternal serum ethanol concentration of 60.8 mg/dL, did not affect maternal weight gain, litter size, or placental or fetal body weight. On Gestational Day 20, rat placental: fetal units were removed by Caesarian section. Placental protein expression, analyzed by 2D-PAGE - tandem mass spectroscopy, identified a total of 1117 protein spots, twenty of which were significantly altered by PAE. To date, fourteen of these PAE-altered proteins have been identified. Western blotting confirmed the alterations of two of these placental proteins, namely, Annexin-A4 (ANX-A4) and Cerebral Cavernous Malformation Protein 3 (CCM-3). Specifically, PAE elevated ANX-A4 and decreased CCM-3 in placenta. Subsequently, these two proteins were measured in fetal cerebral cortex, along with radiohistochemical studies of VEGF binding and histofluorescence studies of microvascular density in fetal cerebral cortex. PAE elevated ANX-A4 and decreased CCM-3 in fetal cerebral cortex, in a pattern similar to the alterations observed in placenta. Further, both VEGF receptor binding and microvascular density and orientation, measures that are sensitive to reduced CCM-3 expression in developing brain, were significantly reduced in the ventricular zone of fetal cerebral cortex. These results suggest that the expression angiogenesis-related proteins in placenta might serve as a biomarker of ethanol-induced alterations in microvascular development in fetal brain.